Resistivity effect in the vicinity of a coronal magnetic null point - Sabri, S.; Poedts, S. (Frontiers in Astronomy and Space Sciences, 2024)
Introduction: We aim to examine how magnetic resistivity impacts the movement of magnetoacoustic waves near a magnetic null-point in the solar corona.Method: The resistive, nonlinear MHD simulations are solved by the PLUTO code in 2.5D for different amount of the resistivity.Results and Discussion: Propagation of magnetoacoustic waves in the vicinity of a magnetic null point has the potential to create current sheets with high current density excitation and plasmoid generation. During the entire duration of the simulation, it is discovered that plasma density became significant due to the plasmoid and also current density is high for high resistivity. It is depicted that high resistivity also leads to bigger plasmoids or magnetic islands in comparison to small resistivity.